US vs. Euro Area : Who Drives Cross-Border Bank Lending to EMs? - Cerutti, Eugenio (IMF Working Papers; Working Paper, 2019)
This paper analyzes the drivers of cross-border bank lending to 49 Emerging Markets (EMs) during the period 1990Q1-2014Q4, by assessing the impact of monetary, financial and real sector shocks in both the US and the euro area. The literature has traditionally highlighted the influence of US monetary policy on driving cross-border bank flows, and more recently the importance of both US and Euro Area (EA) financial/banking sectors' related variables. Our contribution is the simultaneous analysis of the role of these US and EA drivers, as well as their interactions with real sector shocks. We corroborate the negative impact of US monetary policy tightening on cross-border lending to EMs, but we find that EA monetary policy seems to have an impact mostly on Emerging Europe, reflecting the fact that cross-border lending to most other EM regions is dollar denominated. We also find that real sector shocks in both the US and EA trigger an increase in cross-border lending, but less in EA when modeling the financial sector. Finally, for financial sector shocks, such as those associated with a decrease in bank leverage, our results indicate a broad-based overall contraction of cross-border lending if the shock originates in the US, and heterogenous effects across borrowing regions if the shock originates in the EA.